Pembatalan Sepihak Akta Kuasa Khusus Dari Pemberi Kuasa Kepada Penerima Kuasa Terkait Dengan Kredit Modal Kerja Konstruksi - Aldisahr, M. Dafi Siddiq; Yahanan, Annalisa; Samawati, Putu (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2024)
Regarding the legal consequences of unilaterally canceling a power of attorney in the case of working capital loans for construction, special requirements must be met by the bank when lending working capital for construction projects so that it is not canceled and sued unilaterally. This can be done with a power of attorney if it can be proven that the person giving the power of attorney is not carrying out their duties properly. The legal consequences of unilaterally revoking the special authority law are administrative sanctions and judicial revocation of the special authority law. Special requirements for granting working capital credit are met with two-way verification, especially for parties who provide special authority. This is to avoid further legal problems and the principal has the right to take legal action if his representative does not meet the requirements.